Karakterisasi Biopolimer Kitosan Hasil Deasetilasi Limbah Kepiting Rajungan (Portunus Sanginolentus) Menggunakan NaBH4 Dalam NaOH - Hasanela, Nurani; Tanasale, Matheis F.J.D.P.; Tehubijuluw, Helna (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
The chitosan isolation from crab crab waste (Portunus sanginolentus) has been carried out. Chitin production is carried out by the de-proteination, demineralization and depigmentation processes. Chitosan biopolymer is produced from chitin through de-acetylation method using base solution (NaOH) and the addition of NaBH4 which aims to increase the degree of de-acetylation (DD) of chitosan. The results of 25 g of chitin obtained chitosan amounted to 16.67 g (66.68%). Chitin and Chitosan were identified by a Fourier Transform Infrared (FT-IR) spectrophotometer.